Exploring ChatGPT’s potential in the clinical stream of neurorehabilitation - Maggio, Maria Grazia; Tartarisco, Gennaro; Cardile, Davide; Bonanno, Mirjam; Bruschetta, Roberta; Pignolo, Loris; Pioggia, Giovanni; Calabrò, Rocco Salvatore; Cerasa, Antonio (Frontiers in Artificial Intelligence, 2024)
In several medical fields, generative AI tools such as ChatGPT have achieved optimal performance in identifying correct diagnoses only by evaluating narrative clinical descriptions of cases. The most active fields of application include oncology and COVID-19-related symptoms,2 with preliminary relevant results also in psychiatric and neurological domains. This scoping review aims to introduce the arrival of ChatGPT applications in neurorehabilitation practice, where such AI-driven solutions have the potential to revolutionize patient care and assistance. First, a comprehensive overview of ChatGPT, including its design, and potential applications in medicine is provided. Second, the remarkable natural language processing skills and limitations of these models are examined with a focus on their use in neurorehabilitation. In this context, we present two case scenarios to evaluate ChatGPT ability to resolve higher-order clinical reasoning. Overall, we provide support to the first evidence that generative AI can meaningfully integrate as a facilitator into neurorehabilitation practice, aiding physicians in defining increasingly efficacious diagnostic and personalized prognostic plans.